(3GdLGeY aj TQM GdJMQjQs - (3CHhGdMSjf RjO Hf eMeOs; (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdELGRGJ s
(3BNQgG (B:s
(3BNQg ef HGH (B" (3GdTgGOI Ydi GdYJb (B" (3bhdg (B: (3hEfeG bdfG CfgG JbY Ydi hLg GdMSHI dCfgG JYdbJ HeG hUdi Gddg Ydi eMeO hBdg hSde s
(3ef KeGfjI CLRGAs
(3GdfSNI ebGHdI Ohf JGQjNs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
Keywords: (3Gdabg GdESdGejs